Pembinaan Peningkatan Kualitas Guru dalam Menyusun RPP oleh Kepala Sekolah Melalui Program Pembinaan CLCK (Contoh, Latihan, Control, Kerja Mandiri) di SMP Negeri 3 Setia Bakti Kabupaten Aceh Jaya Tahun Pelajaran 2021 – 2022 - Yuniarna (Pencerah, 2021)
The Purpose of this action research is to improve the competence of teachers of SMP Negeri 3 Setia Bakti, Setia Bakti District, Aceh Jaya Regency in the program of preparing lesson plans by applying the CLCK method. The School Development Program which is more commonly called the School Development Plan (RPS) contains long term, medium term, short term programs. These programs serve as a benchmark for school development. The preparation of learning implementation plans is very important, because good learning management greatly influences the preparation of Learning Implementation Plans according to indicators. The advantage of CLCK is that teachers are given examples in making lesson plans and after that they practice with the Principal and the activities carried out do not depend on others. The success of this action is due to the need for a thorough understanding of RPP. With a good understanding, the application of the CLCK Guidance Model to Subject Teachers at SMP Negeri 3 Setia Bakti, Setia Bakti District, Aceh Jaya Regency can optimize teachers' understanding of RPP through intensive coaching in the RPP Preparation program. Then the subjects in this study were subject teachers, totaling 6 people at SMP Negeri 3 Setia Bakti, Setia Bakti District, Aceh Jaya Regency with data collection techniques through observation and interviews. As for the results of the School Action Research, there are 1 teacher who is classified as very active and 5 people are classified as active, based on the results of observations in cycle II. Class teachers at SMP Negeri 3 Setia Bakti, Setia Bakti District, Aceh Jaya Regency have been creative in making Learning Implementation Plans, so that the Development Model CLCK in the Program for Preparation of Learning Implementation Plans at SMP Negeri 3 Setia Bakti, Setia Bakti District, Aceh Jaya Regency can improve teacher competence and teacher opinions are very useful for fostering CLCK in the KBM Implementation program for Middle Schools guided by the author